2020
DOI: 10.31410/eman.2020.171
|View full text |Cite
|
Sign up to set email alerts
|

Competition Law in Digital Era – How to Define the Relevant Market?

Abstract: Competition law serves as an important tool for regulation of undertakings. In order to conduct a competition law analysis, one must first define the relevant market. However, this task is becoming more intricate in today’s digital era, especially in relation to so-called zero-price markets. These markets are characterised as markets where users of products or services do not pay for the use, at least they do not pay by money. This paper asks how to define relevant market in such case. Three methods of relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Methods used for market definition are usually categorised to two groupsquantitative (comprising SSNIP test and SSNDQ test) and qualitative methods (Patakyová, 2020). Each of the methods has its advantages and disadvantages (Patakyová, 2020) and, as a matter of fact, there is no perfect method universally applicable to all cases.…”
Section: Methods Of Market Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods used for market definition are usually categorised to two groupsquantitative (comprising SSNIP test and SSNDQ test) and qualitative methods (Patakyová, 2020). Each of the methods has its advantages and disadvantages (Patakyová, 2020) and, as a matter of fact, there is no perfect method universally applicable to all cases.…”
Section: Methods Of Market Definitionmentioning
confidence: 99%
“…To use the qualitative method of relevant market definition means to focus on distinctive characteristics of products (Patakyová, 2020); among them the Commission emphasises functionality and use of the products/services, 20 conditioning their substitutability. In Google Search (Shopping) case, the Commission concluded that comparison shopping services constitute a distinctive relevant product market, not including merchant platforms or offline shopping comparison tools that "cannot provide users with the same amount of information, level of reactivity and service as comparison shopping service."…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Например, в рамках данного теста может оцениваться поведение пользователей в случае изменения производительности платформы или объема собираемых персональных данных. Кроме того, измерение качества услуг может быть весьма субъективным и требовать доступа к большому объему информации (Patakyová, 2020).…”
Section: второй этап -разработка нормативных правил конкуренции на ци...unclassified
“…From the Commission's report one may conclude that the proposed way is to rather focus on the theories of harm and indication of anticompetitive strategies than on the strict definition of the relevant market. This seems to be an elegant solution, however, it is not clear how the need for the relevant market definition can be circumvented in a competition law analysis (Patakyová, 2020a).…”
Section: The Antitrust Part Of Eu Competition Law and Digitalisation-an Overviewmentioning
confidence: 99%